What do we know about the future of crop pests and pathogens in relation to food systems? - Petsakos, Athanasios; Montes, Carlo; Pequeno, Diego Notelo Luz; Schiek, Benjamin; Sonder, Kai (CGIAR System Organization, 2022)
Key messages - Crop pests and pathogens (P&P) can cause substantial yield losses and pose a threat to global food security. Losses at regional level can even exceed 40% for some crops like maize and rice. - Most studies show that warmer climate creates a conducive, albeit spatially variable, environment for P&P spread. However, existing foresight research is largely biophysical in nature and focuses on individual pathosystems, examined mostly at national level. As such, projections of the magnitude of economic impacts of changing patterns of P&P are missing. - Global assessment of model-based historical and future P&P impacts on food systems remains constrained by the small number of available models that can estimate yield losses under contrasting climate and agroecological conditions. - Further efforts are needed to improve data accessibility, model versatility, and simulation platforms, and to establish international observation and modeling networks.